Implementation of Gamified Programming Learning Assistant System - Sandi Kyaw, Htoo Htoo; Kaneko, Keiichi; Funabiki, Nobuo; Kao, Wen-Chung (Proceedings of IEEE International Symposium on Consumer Electronics, 2025)
Despite the rapid growth of the ICT sector, there is a gap between it and STEM education, resulting in high dropout rates in computer science and engineering programs. This has led to many vacancies in the ICT job market. A major challenge is that traditional teaching methods fail to engage students in difficult and abstract STEM subjects like programming. To overcome this, innovative technology-enhanced learning solutions are needed. In the past, we created a Programming Learning Assistant System (PLAS) to help novice students learn programming. PLAS provides various types of exercises to develop code reading and writing skills at different levels. In this paper, we implement the gamification into PLAS to enhance students' understanding of programming concepts, boost their confidence, spark their interest in STEM fields, and increase engagement in the course through interactive and stimulating scenarios.